Knowledge and Attitudes of Young Women about the First 1000 Days of Life (HPK) in Stunting Prevention - Sarliana; Yuli Admasari (Universitas STRADA Indonesia, 2022)
Stunting is a chronic nutritional problem, globally stunting affects around 21.3% of. Nationally, the prevalence of stunting is 24.4%, which is still far from the government's target of 14% in 2024. The government's efforts to improve nutrition include the Nutrition Improvement Movement program in the first 1000 days of life or the 1000 HPK Movement. Good knowledge and attitude regarding the 1000 HPK is especially important for adolescents, it needs to be equipped early on so that in the future they can prepare for a good quality pregnancy and become the basis for changing nutritional behavior to reduce nutritional problems. The purpose of this research is to know the description of the knowledge and attitudes of young women about 1000 HPK in stunting prevention. The research method used descriptive research carried out in April-June 2022 with a total sample of 100 grade 11 and 12 students at SMAN (State High School) in the Palu city area which was taken using a cluster stratified sampling technique. The research instrument used a questionnaire. Data were analyzed by univariate analysis. The results showed that most of the respondents had sufficient knowledge about 1000 HPK, namely 66%, and had a negative attitude, namely 67%. The conclusion of this study is that the description of the knowledge and attitudes of young women in SMAN Palu city is mostly with sufficient knowledge and a negative attitude. In order to maximize the increase in knowledge and attitudes of young women about 1000 HPK, the school should cooperate with the puskesmas (public health center) to provide health education about 1000 HPK as a form of stunting prevention.